Designing the Management System - Young, Stanley (Academy of Management Journal, 1964)
The article discusses the process of developing a hospital management system. From a systems viewpoint, the hospital under discussion can be considered a total system composed of sub-systems, such as nursing, pharmacy, purchasing, and so forth. A discussion is presented about the development of an organizational structure and the management of responsibility for various component stages of organizational development. The component stages include raising of the organizational problem, assigning the problem to the administrative personnel or department head who is responsible for the particular sphere of operation to which the problem relates, ascertaining the nature of the problem, and searching for improved alternative solutions.